2008
DOI: 10.1177/1534734608324123
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Diabetes Mellitus in Amputations of the Lower Limbs for Gas Gangrene: A Case Report

Abstract: The aim of this study was to examine any association between the presence of diabetes in patients with gas gangrene of the legs and mortality following major lower limb amputation. In a retrospective study, patients submitted to amputation of lower limbs for anaerobic infections were evaluated in the period from January 2005 to January 2007 in the University Hospital de Base in Sao Jose do Rio Preto. All the patients were hospitalized for the treatment of ulcerated lesions of the leg. The study sample consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Another study reported a 44% mortality rate in the 1 st year, 50% in the 2 nd year, and 72% in 6 years. [ 7 , 8 ] Therefore, diabetes is a disease with a high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a 44% mortality rate in the 1 st year, 50% in the 2 nd year, and 72% in 6 years. [ 7 , 8 ] Therefore, diabetes is a disease with a high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…Our case is unique in two aspects. First, as we all know, the responsible organism C. perfringens is mostly associated with development of traumatic gas gangrene but also can be associated with the nontraumatic spontaneous gas gangrene in patients with immunocompromised condition including malignancies and diabetes mellitus [ 2 , 32 ]. Impaired evacuation and motility of the stomach (and the small intestine) has been described in diabetics with long lasting unsatisfactory diabetes compensation, microangiopathic complications, and diabetic autonomous neuropathy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The wound infection rates following major lower limb amputation vary between 13% and 40%. Methicillin-resistant Staphylococcus aureus (MRSA) is the most common cause of post-amputation infections (10,11). The morbidity and mortality rates usually in- crease as a result of MRSA infection in vascular patients (12)(13)(14).…”
Section: Infection Of the Stumpmentioning
confidence: 99%